Method for improving piezomagnetic coefficient of iron-based amorphous alloy based on pulse laser technology
By using pulsed laser technology to etch linear laser marks on the surface of iron-based amorphous alloy, the problems of heating unevenness and material brittleness in traditional annealing process when improving the piezomagnetic coefficient of iron-based amorphous alloy are solved, and the effect of significantly improving the piezomagnetic coefficient of material and maintaining excellent plasticity is achieved. It is suitable for improving the performance of magnetoelectric sensors and magnetoelectric antennas.
Patent Information
- Application Number
- CN202411780225.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-05
AI Technical Summary
When traditional annealing processes increase the piezomagnetic coefficient of iron-based amorphous alloys, there are problems such as uneven heating, difficulty in controlling oxidation, and increased material brittleness, which limits its widespread use in practical applications.
Using a pulsed laser technology method, parallel arranged linear laser marks are etched on the surface of the iron-based amorphous alloy using a pulsed laser beam, and the laser power, score width and spacing are adjusted to improve the piezomagnetic coefficient of the material.
It significantly improves the saturated magnetostrictive coefficient and maximum piezomagnetic coefficient of iron-based amorphous alloy, maintains the excellent plasticity of the material, and avoids the sharp increase in material brittleness. It is suitable for improving the sensitivity and performance of magnetoelectric sensors and magnetoelectric antennas.
Smart Images

Figure CN119634997A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of pulse laser technology, and in particular relates to a method for improving the piezomagnetic coefficient of an iron-based amorphous alloy based on pulse laser technology. Background Art
[0002] Iron-based amorphous alloys are usually metal materials in which the atoms are arranged in a long-range disorder by rapidly cooling the molten metal and inhibiting crystallization. Its material system is generally composed of 80% of metal elements such as Fe, Co, and Ni to ensure its ferromagnetism, and the other part is transition elements such as B, Si, and P that promote the formation of amorphous state. Because its atomic arrangement is long-range disordered and short-range ordered, and there are no defects such as grain boundaries and dislocations, it has a series of excellent soft magnetic properties and magnetostrictive properties, such as high saturation magnetization, high magnetic permeability, low coercive force, low iron loss, and high-voltage magnetic coefficient. In addition, due to its high sensitivity to magnetic field response due to its high-voltage magnetic coefficient, it has become a key functional material in modern industry and science and technology, and is widely used in the manufacture of high-precision magnetoelectric sensors, high-performance magnetoelectric antennas, etc.
[0003] At present, the traditional annealing process is used to enhance the piezomagnetic coefficient of iron-based non-gold alloys. However, although the traditional annealing process can optimize the magnetostrictive properties of iron-based amorphous alloys to a certain extent, improve their magnetoelectric conversion efficiency and stability, the long heating process often leads to uneven heating of the material and difficult to control oxidation. In addition, this heating method will significantly increase the brittleness of the material, thus limiting its widespread use in practical applications.
[0004] Compared with the traditional annealing process, pulsed laser processing technology not only effectively avoids the sharp increase of material brittleness with its rapid thermodynamic response, clean non-contact heat source and highly controllable specific heat treatment process, but also greatly improves the magnetostrictive properties of the material with its simple processing method and excellent improvement effect. So far, there has been no report on the use of periodic linear laser scoring method to improve the piezomagnetic coefficient of iron-based amorphous alloys. Therefore, it is necessary to provide a method for improving the piezomagnetic coefficient of iron-based amorphous alloys based on pulsed laser technology. Summary of the invention
[0005] In view of the above-mentioned problems existing in the prior art, the first technical problem to be solved by the present invention is to provide a method for improving the piezomagnetic coefficient of an iron-based amorphous alloy based on pulsed laser technology. The method has simple processing equipment, simple operation, and low cost. The prepared iron-based amorphous alloy has excellent saturation magnetostriction coefficient and maximum piezomagnetic coefficient. The second technical problem to be solved by the present invention is to provide an iron-based amorphous alloy with improved piezomagnetic coefficient based on pulsed laser technology. The iron-based amorphous alloy has excellent saturation magnetostriction coefficient and maximum piezomagnetic coefficient. The third technical problem to be solved by the present invention is to provide an application of an iron-based amorphous alloy with improved piezomagnetic coefficient based on pulsed laser technology in the field of magnetoelectric sensors and magnetoelectric antennas, so as to improve the sensitivity and performance of magnetoelectric sensors and magnetoelectric antennas.
[0006] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0007] A method for improving the piezomagnetic coefficient of an iron-based amorphous alloy based on pulsed laser technology, wherein a pulsed laser beam is used to etch parallel linear laser marks on the surface of the iron-based amorphous alloy to improve the piezomagnetic coefficient of the iron-based amorphous alloy; wherein the pulsed laser mark spacing is 15 to 30 mm, and the pulsed laser mark width is 5 to 20 mm.
[0008] Furthermore, the central wavelength of the pulse laser is 1064 nm.
[0009] Furthermore, the power of the pulse laser is 5-30W.
[0010] Furthermore, the power of the pulse laser is 15W.
[0011] Furthermore, the pulse laser scoring interval is 20 to 25 mm.
[0012] Furthermore, the width of the pulse laser scoring is 10 to 20 mm.
[0013] Furthermore, the fixed laser frequency is 30kHz, the pulse width is 100ns, and the laser scanning speed is 1000mms -1 .
[0014] Furthermore, the laser etching point spacing is 0.2 mm.
[0015] The iron-based amorphous alloy prepared by the method.
[0016] The method is applied in the field of magnetoelectric sensors and magnetoelectric antennas.
[0017] Beneficial effects: Compared with the prior art, the advantages of the present invention are:
[0018] (1) The present invention processes the surface of the iron-based amorphous alloy by adjusting the laser power, the width and spacing of the periodic linear laser scratches, and the saturation magnetostriction coefficient and the maximum piezomagnetic coefficient are significantly improved, while the material still maintains the amorphous structure characteristics and has excellent plasticity;
[0019] (2) Compared with isothermal annealing and other treatment methods, the material of the present invention still has excellent plasticity. The present invention uses pulsed laser technology with rapid thermodynamic response, clean non-contact heat source and highly controllable specific heat treatment process to effectively avoid the sharp increase of material brittleness. It also greatly improves the magnetostrictive properties of the material with its simple processing method and excellent improvement effect.
[0020] (3) The processing equipment of the present invention is simple, easy to operate, low in cost and fast in processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the SEM image of the iron-based amorphous alloy sample after pulse laser treatment when the laser power is 15W;
[0022] Figure 2 This is the XRD pattern of the Fe-based amorphous alloy sample after pulsed laser treatment when the laser power is 15W;
[0023] Figure 3 This is a graph showing the variation of the saturation magnetostriction coefficient / maximum piezomagnetic coefficient of the samples after being treated with different laser powers according to the present invention;
[0024] Figure 4 This is a graph showing the magnetostriction coefficient test results of samples treated with different laser powers according to the present invention;
[0025] Figure 5 This is a graph showing the maximum piezomagnetic coefficient test results of samples treated with different laser powers according to the present invention;
[0026] Figure 6 This is a graph showing the variation of the saturation magnetostriction coefficient of the sample when the laser scoring interval is fixed and the scoring width is changed;
[0027] Figure 7 This is a graph showing the variation of the maximum piezomagnetic coefficient of the sample when the laser scoring interval is fixed and the scoring width is changed in the present invention;
[0028] Figure 8 This is a graph showing the variation of the saturation magnetostriction coefficient of the sample when the laser scoring width is fixed and the scoring spacing is changed;
[0029] Fig. 9 This is a graph showing the variation of the maximum piezomagnetic coefficient of the sample when the laser scoring width is fixed and the scoring spacing is changed in the present invention;
[0030] Fig.10This is a graph showing the magnetostriction coefficient test results of the sample when the laser scoring interval is fixed and the scoring width is changed in the present invention;
[0031] Fig.11 This is a graph showing the magnetostriction coefficient test results of a sample when the laser scoring width is fixed and the scoring spacing is changed in the present invention;
[0032] Fig.12 This is a test result diagram of the piezomagnetic coefficient of the sample when the laser scoring interval is fixed and the scoring width is changed in the present invention;
[0033] Fig.13 This is a test result diagram of the piezomagnetic coefficient of the sample when the laser scoring width is fixed and the scoring spacing is changed in the present invention;
[0034] Fig.14 This is a comparison chart of the detection limits of weak magnetic fields of the magneto-electric composite material prepared by the present invention using untreated and pulsed laser-treated iron-based non-gold alloy. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described below in conjunction with specific embodiments. In the following examples, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0036] The iron-based amorphous alloy used in the following examples is sourced from the AYFA-M model iron-based amorphous alloy material of Qingdao Yunlu Advanced Materials Technology Co., Ltd.
[0037] The fiber laser equipment used in the following examples is a Zhongtian Laser 30W laser marking machine, the central wavelength of the laser is 1064nm, during the processing, the fixed laser frequency is 30kHz, the pulse width is 100ns, and the laser scanning speed is 1000mms -1 The laser etching point spacing is 0.2mm. By adjusting the laser power, the width and spacing of the periodic linear laser marks, the size of 125×20mm 2 The rectangular Fe-based amorphous alloy surface is processed.
[0038] The following examples use the Nanjing Hepu dynamic signal test and analysis system HP-DS8125 to test the change of the magnetostriction coefficient (λ) of the material in a DC magnetic field of 0-30Oe, and use d 33,m =dλ / dH, calculate its piezomagnetic coefficient (d 33,m ). The magnetostriction coefficient is tested by strain gauge resistance measurement method, and the specific test method is as follows:
[0039] (1) Paste the resistance strain gauge onto the sample after pulse laser treatment;
[0040] (2) The sample is connected to form a current loop and placed in the central area of the customized Helmholtz coil. The DC power supply is ITECH IT6302 DC power supply with an output current range of 0-3A. The coil constant of the customized Helmholtz coil is K B =10Oe / A, can generate a DC magnetic field of 0-30Oe;
[0041] (3) During the process of magnetic field change, the strain Δl / l of the sample under the action of the external magnetic field is transmitted to the resistance strain gauge through force and converted into resistance change ΔR / R. The characteristics of the strain gauge are ΔR=R i -R, where K is the strain coefficient of the resistance strain gauge, R is the resistance of the strain gauge when there is no external magnetic field, and R i is the resistance of the strain gauge when there is an external magnetic field. The magnetostriction coefficient of the sample can be obtained by the resistance change of the strain gauge. Then the corresponding relationship between the magnetostriction coefficient of the sample and the magnetic field intensity is obtained;
[0042] (4) Based on the corresponding relationship between magnetostriction coefficient and magnetic field intensity, using d 33,m =dλ / dH, the corresponding relationship between the piezomagnetic coefficient and the magnetic field intensity can be obtained.
[0043] Example 1
[0044] The method of improving the piezomagnetic coefficient of iron-based amorphous alloy with different laser powers based on pulsed laser technology is as follows:
[0045] The fiber laser equipment is used to produce a 125×20mm 2 The rectangular iron-based non-gold alloy surface is etched with parallel linear laser marks using a pulsed laser beam, where the fixed laser frequency is 30kHz, the pulse width is 100ns, and the laser scanning speed is 1000mms -1 The laser etching point spacing is 0.2mm, the pulse laser center wavelength is 1064nm, the fixed scratch spacing is 25mm, the scratch width is 10mm, and the laser power is set to 5W, 10W, 15W, 20W, 25W and 30W respectively. Six groups of samples treated with different pulse laser powers are obtained. The samples are characterized by SEM and XRD. The results are shown in Figure 1 and 2 The six groups of samples after treatment were attached with resistance strain gauges and placed in a DC magnetic field of 0-30Oe to test their magnetostriction coefficients. The results are shown in Table 1 and Figures 3 to 5 shown.
[0046] Table 1 Saturation magnetostriction coefficient and maximum piezomagnetic coefficient of samples treated with different laser powers and the percentage change compared with the un-marked sample
[0047]
[0048] Depend on Figure 1 It can be seen that by using a scanning electron microscope (SEM) to characterize the iron-based amorphous alloy sample after pulse laser treatment, periodically arranged laser scoring points with a diameter of 70 μm can be observed.
[0049] Depend on Figure 2 It can be seen that the iron-based amorphous alloy sample after pulse laser treatment is characterized by X-ray diffraction (XRD), and the iron-based amorphous alloy still maintains the amorphous structure characteristics.
[0050] Depend on Figures 3 to 5 As shown in Table 1, the saturation magnetostriction coefficient and maximum piezomagnetic coefficient of the samples treated with pulsed lasers of different powers have significant changes compared to the untreated samples, and generally show a trend of first increasing and then decreasing. Among them, when the laser power is 15W, the saturation magnetostriction coefficient and maximum piezomagnetic coefficient of the sample are increased the most. When measuring the saturation magnetostriction coefficient of the sample, its maximum magnetostriction coefficient increased from 24.84ppm to 34.76ppm, an increase of 39.94%; when calculating the maximum piezomagnetic coefficient of the sample, its maximum piezomagnetic coefficient increased from 5.85ppm / Oe to 11.23ppm / Oe, an increase of 91.97%.
[0051] Example 2
[0052] The method of improving the piezomagnetic coefficient of iron-based amorphous alloys with different laser scoring widths / spacing based on pulse laser technology is as follows:
[0053] The fiber laser equipment is used to produce a 125×20mm 2 The rectangular iron-based non-gold alloy surface is etched with parallel linear laser marks using a pulsed laser beam, where the fixed laser frequency is 30kHz, the pulse width is 100ns, and the laser scanning speed is 1000mms -1 The laser etching point spacing is 0.2mm, the pulse laser center wavelength is 1064nm, the fixed laser power is 15W, the scratch spacing is set to 15mm, 20mm, 25mm and 30mm, and the scratch width is 5mm, 10mm, 15mm and 20mm, respectively. 16 groups of samples with different pulse laser spacing and widths are obtained.
[0054] The 16 groups of samples treated with pulsed laser were attached with resistance strain gauges, placed in a DC magnetic field of 0-30Oe to test their magnetostriction coefficients, and their piezomagnetic coefficients were calculated. The results are shown in Tables 2, 3 and Figures 6 to 13Table 2 Saturation magnetostriction coefficient of samples after different laser scoring parameters and the percentage change compared with the unscored samples
[0055]
[0056] Table 3 Maximum piezomagnetic coefficient of samples treated with different laser scoring parameters and percentage change compared with unscored samples
[0057]
[0058]
[0059] From Tables 2, 3 and Figures 6 to 13 It can be seen that the saturation magnetostriction coefficient and the maximum piezomagnetic coefficient of the samples treated with pulsed lasers of different scratch spacing and widths have significant changes compared to the untreated samples. When the laser scratch spacing is fixed and the laser scratch width is increased, the saturation magnetostriction coefficient of the sample generally shows an increasing trend, and the maximum piezomagnetic coefficient generally shows a trend of first increasing and then decreasing; when the laser scratch width is fixed and the laser scratch spacing is increased, the saturation magnetostriction coefficient and the maximum piezomagnetic coefficient of the sample generally show a trend of first increasing and then decreasing. Among them, when the scratch spacing is 20-25mm and the scratch width is 10-20mm, the saturation magnetostriction coefficient and the maximum piezomagnetic coefficient of the sample are relatively increased. When measuring the saturation magnetostriction coefficient of the sample, its maximum saturation magnetostriction coefficient increased from 24.84ppm to 34.77ppm, an increase of 39.98%; when calculating the maximum piezomagnetic coefficient of the sample, its maximum piezomagnetic coefficient increased from 5.85ppm / Oe to 11.06ppm / Oe, an increase of 89.06%. In summary, the method of the present invention can effectively improve the piezomagnetic coefficient of the iron-based amorphous alloy material.
[0060] Example 3
[0061] The method of improving the weak magnetic detection capability of magnetoelectric composite materials with iron-based amorphous alloys based on pulsed laser technology is as follows:
[0062] 1) Principle of weak magnetic detection of magnetoelectric composite materials:
[0063] The magnetoelectric composite material is based on the magnetoelectric coupling effect. It uses magnetostrictive materials (iron-based amorphous alloys) to generate magnetostrictive strain under the action of an external magnetic field, and uses strain coupling at the interface to transfer the elastic strain to the piezoelectric material (PZT-5H). This induces bound charges on the surface of the piezoelectric material, thereby realizing the conversion of external weak magnetic signals into electrical signals.
[0064] 2) Preparation process of magnetoelectric composite materials:
[0065] The size is 125×20mm2 The rectangular iron-based non-gold alloy surface is etched with parallel linear laser marks using a pulsed laser beam, where the fixed laser frequency is 30kHz, the pulse width is 100ns, and the laser scanning speed is 1000mms -1 , the laser etching point spacing is 0.2mm, the pulse laser center wavelength is 1064nm, the fixed laser power is 15W, the fixed scratch spacing is 25mm, the scratch width is 10mm, and 24 groups of pulse laser processed samples are obtained. Use epoxy resin 105 / 206 to bond every 3 groups of samples and dry them at a constant temperature of 50℃ for 8 hours, for a total of 8 groups. Use epoxy resin 105 / 206 to bond the dried samples to a 40×20mm 2 The piezoelectric material (PZT-5H) was bonded to form a magnetoelectric composite material with LT structure: iron-based non-gold alloy / piezoelectric ceramic / iron-based non-gold alloy, and dried at a constant temperature of 50°C for 8 hours. There were 4 groups in total, recorded as samples 5 to 8. At the same time, 4 groups of magnetoelectric composite materials made of untreated iron-based non-gold alloy were prepared using the same production process for subsequent comparative testing, recorded as samples 1 to 4.
[0066] The present invention tests the magnetoelectric charge coefficient of the magnetoelectric composite material prepared from the untreated and pulsed laser treated iron-based non-gold alloy. The effective value of the charge induced on the sample is measured by a charge amplifier, and combined with the effective value of the applied AC magnetic field, the magnetoelectric charge coefficient can be measured by The magnetoelectric charge coefficient was determined. The results are shown in Tables 4 and 5.
[0067] Table 4 Performance parameters of magnetoelectric composite materials using untreated Fe-based amorphous alloys
[0068]
[0069] Table 5 Performance parameters of magnetoelectric composites of Fe-based amorphous alloys treated with pulsed laser
[0070]
[0071] As shown in Table 4 and Table 5, the average magnetoelectric charge coefficient of the four groups of magnetoelectric composite materials prepared from untreated iron-based amorphous alloys under quasi-static state (1kHz) is 3425.3 pC / Oe, and the average magnetoelectric charge coefficient of the four groups of magnetoelectric composite materials prepared from iron-based amorphous alloys treated by pulsed laser is 4856.8 pC / Oe, which is improved by 41.79%. It is proved that the iron-based amorphous alloy treated by pulsed laser can improve the magnetic field detection capability of the magnetoelectric composite material, indicating that the present invention has important application value in manufacturing high-sensitivity magnetoelectric sensors, high-performance magnetoelectric antennas, etc.
[0072] Based on the comparison of magnetoelectric charge coefficients of magnetoelectric composite materials prepared from untreated and pulsed laser treated iron-based amorphous alloys, the present invention also conducts comparative tests on the detection limit capabilities of the two magnetoelectric composite materials for weak magnetic fields. The two magnetoelectric composite materials are placed in an environment where an external AC signal source (weak magnetic field to be measured) is applied, and the electrical response signals of the magnetoelectric composite materials are detected by a phase-locked amplifier (UHFLI600MHz). The results are as follows: Fig.14 shown.
[0073] Depend on Fig.14 It can be seen that the detection limit of the magnetoelectric composite material prepared from the untreated iron-based amorphous alloy to weak magnetic fields is 368pT, and the detection limit of the magnetoelectric composite material prepared from the iron-based amorphous alloy treated by pulsed laser to weak magnetic fields is 123pT, which is 1 / 3 of the weak magnetic field detection limit of the untreated sample. This result not only further verifies the effectiveness of pulsed laser technology in improving the piezomagnetic coefficient of iron-based amorphous alloys, but also fully demonstrates the important role of this technology in improving the weak magnetic detection capability of magnetoelectric composite materials.
[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for improving the piezomagnetic coefficient of an iron-based amorphous alloy based on pulsed laser technology, characterized in that: A pulsed laser beam is used to etch parallel linear laser marks on the surface of an iron-based amorphous alloy to improve the piezomagnetic coefficient of the iron-based amorphous alloy; wherein the pulsed laser mark spacing is 15 to 30 mm, and the pulsed laser mark width is 5 to 20 mm.
2. The method for improving the piezomagnetic coefficient of an iron-based amorphous alloy based on pulsed laser technology according to claim 1, characterized in that: The central wavelength of the pulse laser is 1064 nm.
3. The method for improving the piezomagnetic coefficient of an iron-based amorphous alloy based on pulsed laser technology according to claim 1, characterized in that: The power of the pulse laser is 5-30W.
4. The method for improving the piezomagnetic coefficient of an iron-based amorphous alloy based on pulsed laser technology according to claim 3, characterized in that: The power of the pulse laser is 15W.
5. The method for improving the piezomagnetic coefficient of an iron-based amorphous alloy based on pulsed laser technology according to claim 1, characterized in that: The pulse laser scoring interval is 20 to 25 mm.
6. The method for improving the piezomagnetic coefficient of an iron-based amorphous alloy based on pulsed laser technology according to claim 1, characterized in that: The pulse laser scoring width is 10 to 20 mm.
7. The method for improving the piezomagnetic coefficient of an iron-based amorphous alloy based on pulsed laser technology according to claim 1, characterized in that: The fixed laser frequency is 30kHz, the pulse width is 100ns, and the laser scanning speed is 1000mms -1 .
8. The method for improving the piezomagnetic coefficient of an iron-based amorphous alloy based on pulsed laser technology according to claim 1, characterized in that: The laser etching point spacing is 0.2 mm.
9. The iron-based amorphous alloy prepared by the method according to any one of claims 1 to 8.
10. Application of the method according to any one of claims 1 to 8 in the field of magnetoelectric sensors and magnetoelectric antennas.
Citation Information
Patent Citations
Wound magnetic core and method for manufacturing same
CN105074841A
Low-loss amorphous alloy iron core, transformer and manufacturing method
CN117133532A
Amorphous alloy thin band excellent in magnetic characteristic
JP1988300502A
MELT-QUENCHED Fe-BASED SOFT MAGNETIC ALLOY THIN BAND AND MAGNETIC CORE
JP2012174824A
Magneto-strictive torque sensor
US4933580A